The effect of legalization, financing, and provision of raw materials on the development of UMKM business in Palembang City - Putri, Aulia Utami; Mandasari, Lisa; Khairunnisyah, Tuty; Mirani, Dwi (Goodwood Publishing, 2025)
Purpose: The purpose of this study is to investigate the influence of legalization, financing, and raw material provision on the business development of MSME actors in Palembang City Methodology/approach: A quantitative approach was used, employing multiple linear regression analysis. The sample consisted of 92 MSME actors in Palembang City Results/findings: The results showed that legalization significantly impacts business development, with a t-value of 2.150 (greater than 1.660) and a significance value of 0.034 (less than 0.05). Financing also significantly affects business development, with a t-value of 2.101 (greater than 1.660) and a significance value of 0.038 (less than 0.05). The provision of raw materials significantly influences business development, with a t-value of 1.934 (greater than 1.660) and a significance value of 0.032 (less than 0.05). Based on the F-test, the calculated F-value of 3.695 exceeds the F-table value of 2.698 Conclusion: Indicating that the three factors (legalization, financing, and raw material provision) collectively and significantly affect business development. Limitations: The study is limited to MSME actors in Palembang City, which restricts the generalizability of the findings to other regions. Future research could include additional variables to provide a more comprehensive understanding. This study shows that 47.5% of business development is influenced by these factors, while the remaining 52.5% is influenced by other factors. Contribution: This research contributes by examining the simultaneous effects of legalization, financing, and raw material provision on MSME development in Palembang, providing valuable insights often overlooked in previous studies.